Fabrication of mercury (Hg) sensor based on Tire Waste (TW) carbon electrode and voltammetry technique - Baihaqi Baihaqi; Khairi Suhud; Sagir Alva; Eka Safitri; Julinawati Julinawati; Binawati Ginting; Syafrizal Fonna; Ahmad Kamal Arifin; Zulnazri Zulnazri; Nurul Islami (SINERGI, 2023)
Voltammetry is widely used to detect heavy metals such as mercury (Hg). The sensor material influences the results of the voltammetry method. Carbon-based sensors are commonly developed because of their wide potential range, low background current, inexpensive, inert, and suitable for various sensors. Recently, Tire Waste (TW) was chosen as a carbon source for the manufacture of electrodes because it is rich in carbon (88%). The material is easy to obtain, green technology and a carbon source that has not been properly utilized. Separation of carbon material from TW using the pyrolysis method produces 4.32 gr (2.6%) of soot (from 200 gr TW) as a material for making carbon-based Hg sensors. The XRD pattern of TW soot has amorphous phases. SEM topography shows that the surface of TW soot consists of particles that are almost uniform in shape. The estimated particle size is about 0.25 µm. The sensor was made with a mixture of TW soot and paraffin with a 2:1 ratio. Testing the specific value of sensor capacitance using the Cyclic Voltammetry (CV) method showed the presence of cathodic and anodic currents. The Hg deposit occurred at a peak cathodic current at a scan rate of 20 mV/s. The Limit of Detection (LoD) value is 0.0681 ppm and the Limit of Quantitation (LoQ) is 0.229 ppm. Measurement of Hg in natural water samples used river water from the Aceh Jaya sub-district at two points representing the upstream and downstream of the river. The Hg concentrations obtained were 0.000536 ppm and 0.00182 ppm, respectively and were compared with the inspection results using Atomic Absorbance Spectroscopy (AAS), 0.00058 ppm and 0.00186 ppm, respectively. The t-test results of the two Hg measurement methods at a significance level (α) of 5% obtained tcount > ttable (0.0208 <2.306), indicating that there is a significant difference between the two Hg concentration measurement methods for natural water.